2022
DOI: 10.3390/molecules27144401
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferia parviflora Rhizome Extract as Potential Anti-Acne Ingredient

Abstract: Kaempferia parviflora (Black ginger) is used widely in medical fields as an anti-microorganism and anti-inflammation. In this study, the aim was to evaluate the in vitro and in vivo anti-acne efficacy of black ginger extract. The results indicate that the methanol and ethanol extracts showed the highest total phenolic contents, without a significant difference, whereas the n-hexane extract showed the highest total flavonoid content. Nine flavones were detected using UPLC−QTOF−MS, and the ethyl acetate extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Sitthichai et al conducted a study in which volunteers with acne applied twice daily formulations of black ginger with different solvents for 6 weeks and demonstrated significant improvement in acne vulgaris and erythema. 18 As a potential skin-whitening agent, Huang et al 19 assessed the effects of 6-gingerol on mushroom tyrosinase and B16F10 melanoma cells. They demonstrated that 6-gingerol reduced tyrosinase activity and inhibited melanin synthesis in a dosedependent manner.…”
Section: Other Dermatologic Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sitthichai et al conducted a study in which volunteers with acne applied twice daily formulations of black ginger with different solvents for 6 weeks and demonstrated significant improvement in acne vulgaris and erythema. 18 As a potential skin-whitening agent, Huang et al 19 assessed the effects of 6-gingerol on mushroom tyrosinase and B16F10 melanoma cells. They demonstrated that 6-gingerol reduced tyrosinase activity and inhibited melanin synthesis in a dosedependent manner.…”
Section: Other Dermatologic Usesmentioning
confidence: 99%
“…Sitthichai et al. conducted a study in which volunteers with acne applied twice daily formulations of black ginger with different solvents for 6 weeks and demonstrated significant improvement in acne vulgaris and erythema 18 …”
Section: Dermatologic Applicationsmentioning
confidence: 99%
“…KP rhizome, also known as black ginger, contains anti-microorganism, anti-inflammatory, anticancer, antiallergic, anti-osteoarthritis, antioxidant, cardioprotective, neuroprotective, sexual-enhancing, and physicalenhancing activities. [1][2][3][4][5][6] The major active compounds are methoxyflavones and their derivatives. 6 Our previous study demonstrated the inhibitory activity of crude KP extract against Helicobacter pylori, an etiological agent of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most well-known benefits of K. parviflora is its aphrodisiac effects [2,3]. In addition, K. parviflora has also been found to have anti-inflammatory and antioxidant properties [4,5]. These properties help reduce inflammation in the body and protect cells from oxidative stress, which can help prevent chronic diseases such as heart disease and cancer.…”
Section: Introductionmentioning
confidence: 99%